(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
The problem in this activity is the ability to write paragraphs through the Mind Mapping learning model for fifth grade elementary school students. Writing skills in students are not formed suddenly, but writing skills must be trained or practiced continuously, especially by writing paragraphs. Writing paragraphs is a basic activity in writing, by discussing an idea or one main idea. In general, a paragraph begins with the main idea and continues with an explanatory sentence that provides an explanation to support or develop the main idea. Explanatory sentences in the sequence of paragraphs must be related to the main idea, either in explaining or completing. So that paragraphs are arranged systematically and logically. With these problems it is necessary to use the right learning model to overcome these problems. One learning model that is suitable for improving the ability to write paragraphs is the mind mapping learning model.